(untitled) (Islamic Sciences Journal, 2026)
This research aims to clarify the concept of intellectual extremism and its most significant effects within the university environment, as well as to identify the factors that contribute to its emergence among university students. It also seeks to highlight the academic and educational role played by university professors in limiting and addressing this phenomenon. The importance of this study stems from the fact that the university is an academic and educational institution that plays a vital role in shaping students’ intellectual awareness, making it an influential environment for promoting the values of moderation and balance and for confronting intellectual deviations. The study concludes that confronting intellectual extremism within university settings requires the integration of educational and pedagogical efforts, the activation of awareness programs and academic seminars, and the development of students’ critical thinking skills. It also emphasizes the importance of supporting university initiatives that promote the values of moderation and tolerance, thereby contributing to building an aware university environment capable of confronting manifestations of intellectual extremism